The potential moderating role of supply chain capabilities on the relationship between supply chain technology and concurrent engineering in product design - Singhry, Hassan Barau; Abd Rahman, Azmawani; Ng, Siew Imm (ExcelingTech Publishers, 2014)
Today’s business and competitive environment put pressures on firms to adopt new technologies, processes, and competences. Firms with strong technological capabilities generates more value from technology investment and achieve higher order of collaborative gains in product design. The aim of this paper is to improve a conceptual framework of the influential determinant of product design in supply chain. Through an intensive literature review, the paper develops a conceptual model of the relationships between supply chain technology, capabilities, and concurrent engineering in new product design. The study has practical implications to managers and practitioners in supply chain management. The study also contributes to existing literature and theory of product design and development.